2018
DOI: 10.4103/sni.sni_181_18
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth and progression of multiple calcifying pseudoneoplasms of the neuraxis: Case report

Abstract: Background:Calcifying pseudoneoplasms of the neuraxis (CAPNONs) are clinically rare, nonneoplastic, noninflammatory-calcified lesions of the central nervous system. Resection of a lesion usually indicates good prognosis without recurrence. However, we experienced a unique case of CAPNON that repeatedly recurred after resection.Case Description:A 52-year-old woman with recurrence of an undiagnosed brain tumor, which was resected 12 years ago, was admitted to our institution. Three calcifying lesions along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Reports of dual pathology or ‘collision’ lesions include pericallosal lipoma, meningioangiomatosis, dysembryoplastic neuroepithelial tumour, ependymoma, low‐grade glioma, and meningioma 10,34‐39 . Rarely, multiple CAPNON lesions have been identified in the same patient with dissemination in space and/or time 39‐42 …”
Section: Discussionmentioning
confidence: 99%
“…Reports of dual pathology or ‘collision’ lesions include pericallosal lipoma, meningioangiomatosis, dysembryoplastic neuroepithelial tumour, ependymoma, low‐grade glioma, and meningioma 10,34‐39 . Rarely, multiple CAPNON lesions have been identified in the same patient with dissemination in space and/or time 39‐42 …”
Section: Discussionmentioning
confidence: 99%
“…9 CAPNON is most often solitary, except for 4 reported cases with multiple intracranial lesions. [10][11][12][13] Here, we present a case of CAPNON at the right posterior skull base in a 44-year-old woman. To our knowledge, only 27 cases of CAPNON at the skull base have been reported between 1989 and 2020 (Table 1), 2,[4][5][6]8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] with ages ranging from 19 to 70 years (median age: 50 years) and a male predominance (malefemale ratio, 1.7:1).…”
Section: Discussionmentioning
confidence: 94%
“…6,8,28 In addition, it has been reported that CAPNON does not display mitoses. 9,13 In most cases, the palisading epithelioid cells surrounding the matrix are positive for vimentin, with variable intensity, and EMA may be positive in a few cells. Glial fibrillary acidic protein and S100 are negative in CAPNON.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…On CT, CAPNON presents as well-defined solid lesions that are completely calcified or show calcification at the periphery. 7 On MRI, CAPNON typically shows hypointense signals on T1-and T2-weighted sequences, with minimal or no contrast enhancement, and edema is rarely observed. 10 However, in our patient, the lesion in the right frontal lobe appeared hypointense on T1-weighted images, and hypointense on T2-weighted FLAIR images with a slightly isointense signal in the rim, together with the adjacent hyperintense area indicative of edema.…”
Section: Discussionmentioning
confidence: 99%